STEL (System Thinking and ESD Learning) Model : Developing Elementary School Students' Systems Thinking Skills - Ahmad Mulyadiprana; Ghullam Hamdu; Ade Yulianto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This study aims to improve elementary school students' systems thinking skills through sustainable development-oriented learning. This research method uses an experiment with a quantitative approach to test the effectiveness of developing elementary school students' systems thinking skills. The learning prepare expressly employments the STEL (System Thinking & ESD Learning) learning show which is taken after by 19 basic school understudies in Tasikmalaya City, West Java. The instrument used is an essay test consisting of 8 questions with an assessment rubric made on a scale of 1-3, then the value processing is converted into a maximum score of 100 so that it is easier to analyze the value of elementary school students' systems thinking skills. Information collection was carried out some time recently and after the execution of learning utilizing the STEL model. Generally, the comes about of the pretest-posttest think about of students' systems thinking abilities experienced an insignificant increment. These results provide an overview that elementary school students' systems thinking skills can be developed, only the pretest results of 37.47 and posttest of 49.89 certainly show the results of an increase in students' systems thinking. An important note from the results of this study provides information that systems thinking skills can be developed gradually and sustainably. The learning process through the STEL learning model will prepare understudies to discover the center of environmental issues efficiently and empower understudies to pay more consideration to the affect of each of their exercises and take more mindful activities as it were for environmental, social and economic sustainability.